Moderate Frequency Resistance and Balance Training Do Not Improve Freezing of Gait in Parkinson's Disease: A Pilot Study - Schlenstedt, Christian; Paschen, Steffen; Seuthe, Jana; Raethjen, Jan; Berg, Daniela; Maetzler, Walter; Deuschl, Günther (Frontiers in Neurology, 2018)
Background and aim: Individuals with Parkinson’s disease (PD) and Freezing of Gait (FOG) have impaired postural control, which relate to the severity of FOG. The aim of this study was to analyze whether a moderate frequency resistance (RT) and balance training (BT), respectively, are effective to diminish FOG. Methods: This sub-analysis of a randomized-controlled training-intervention study of PD patients with and without FOG reports about results from FOG patients. Twelve FOG-patients performed RT and 8 BT (2x/week, 7 weeks). Testing was performed prior and post intervention. FOG was assessed with the FOG-Questionnaire (FOGQ) and with the FOG-score of a FOG provoking walking course. Balance performance was evaluated with the Fullerton Advanced Balance (FAB) scale. Tests were conducted by raters blinded to group allocation and assessment time (only FOG-score and FAB scale). Results: For the FOGQ and FOG-score, no significant differences were found within and between the two training groups (p>0.05) and effect sizes for the improvements were small (r<0.1). Groups did not significantly improve in the FAB scale. FOG-score changes and FAB scale changes within the RT group showed a trend towards significant negative correlation (Rho=-0.553, p=0.098). Conclusions: Moderate frequency RT and BT was not effective in reducing FOG in this pilot study. The trend towards negative correlation between changes in FOG-score and FAB scale suggests an interaction between balance (improvement) and FOG (improvement). Future studies should include larger samples and high frequency interventions to investigate the role of training balance performance to reduce the severity of FOG.